2020
DOI: 10.1017/s0954394520000101
|View full text |Cite
|
Sign up to set email alerts
|

A corpus-based quantitative analysis of twelve centuries of preterite and past participle morphology in Dutch

Abstract: Germanic preterite morphology has been the subject of a bewildering number of studies, looking especially at the competition between the so-called strong inflection (operating with ablaut), and the so-called weak inflection (operating with suffixation). In this study over 250,000 observations from twelve centuries of Dutch were analyzed in a generalized linear mixed-effect model gauging the effects of a multitude of language-internal factors, ranging from various frequency measures to various form-related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The advantage of corpus-based studies is that they have higher ecological validity, as they work with naturally occurring data. Additional advantages are (i) the scale of the data, which are usually extracted from corpora that cover millions to even billions of words, reducing the risk of underpowered results; (ii) the high replicability, as the corpora are usually publicly available; and (iii) the possibility to gather data from the past, alleviating the present-day bias to some extent (Bergs & Hoffmann, 2017;De Smet & Van de Velde, 2020;Hundt, Mollin, & Pfenninger, 2017;Petré & Van de Velde, 2018;Wolk, Bresnan, Rosenbach, & Szmrecsanyi, 2013), though the difficulties and obstacles in historical corpus linguistics should not be underestimated (Van de Velde & Peter, 2020). These advantages assuage Yarkoni's concerns about generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of corpus-based studies is that they have higher ecological validity, as they work with naturally occurring data. Additional advantages are (i) the scale of the data, which are usually extracted from corpora that cover millions to even billions of words, reducing the risk of underpowered results; (ii) the high replicability, as the corpora are usually publicly available; and (iii) the possibility to gather data from the past, alleviating the present-day bias to some extent (Bergs & Hoffmann, 2017;De Smet & Van de Velde, 2020;Hundt, Mollin, & Pfenninger, 2017;Petré & Van de Velde, 2018;Wolk, Bresnan, Rosenbach, & Szmrecsanyi, 2013), though the difficulties and obstacles in historical corpus linguistics should not be underestimated (Van de Velde & Peter, 2020). These advantages assuage Yarkoni's concerns about generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…A lot is known about the factors that determine this shift. Most importantly, it has been shown that verbs with a high token frequency tend to weaken less than verbs with a low token frequency (Lieberman et al 2007 for English; Carroll et al 2012 for German; De Smet & Van de Velde 2019 for Dutch), though many other factors play a role as well (De Smet & Van de Velde 2020b). Much less is known about the factors determining whether a varying verb shows a strong or weak verb form in a specific context.…”
Section: Introductionmentioning
confidence: 99%